A Comparative Study of Religious Orientation, Well-being, and Identity Crisis among Adolescents Residing in Welfare Centers and Normal Adolescents in Rasht City - Fatemeh Pouragha (Journal of Modern Psychology, 2022)
The Purpose of this research was to compare religious orientation, well-being, and identity crisis among adolescents residing in welfare centers and normal adolescents. This study employed a causal-comparative research design. The statistical population of the research included all adolescents residing in welfare centers and normal adolescents in Rasht city. For this purpose, 37 adolescents residing in welfare centers and 38 normal adolescents were selected using convenience sampling method. The instruments used in this study were the religious orientation questionnaire, Oxford happiness questionnaire (OHQ), and identity crisis questionnaire. The obtained data were analyzed using independent t-tests to compare the two groups. The results of the independent t-tests indicated significant differences between the two groups of children residing in welfare centers and normal children in terms of total score of identity crisis, total score of well-being, and religious orientation. Based on the findings, it can be concluded that the upbringing of adolescents in normal families is important for enhancing religious orientation, increasing self-confidence, and reducing identity crisis. Based on the findings, it can be concluded that the upbringing of adolescents in normal families is important for enhancing religious orientation, increasing self-confidence, and reducing identity crisis.